PENGARUH LINGKUNGAN KERJA FISIK, LINGKUNGAN KERJA NON FISIK, DAN LOCUS OF CONTROL INTERNAL TERHADAP KINERJA PEGAWAI PADA KANTOR BADAN KESATUAN BANGSA DAN POLITIK KABUPATEN PASURUAN - Lestari, Mega Dewi; Sutikno, Bambang; Fibriyani, Vita (Indonesian Journal of Economy, Business, Entrepreneuship and Finance, 2025)
The National Unity and Politics Agency of Pasuruan Regency is an organization that has a position as a supporting element for the Regent's duties, in the field of unity and politics. This study aims to determine the influence of the physical work environment, non-physical work environment, and internal locus of control on employee performance partially and simultaneously. The population used was 37 employees with multiple linear regression analysis. The results of the study showed that the physical work environment, non-physical work environment and internal locus of control on employee performance simultaneously showed a calculated F value of 29.069> F table 2.89 and a significance value of 0.00 <0.05 and R2 0.731 or 73.1%. Partially, the physical work environment has a significant effect on employee performance with a sig. value of 0.00 <0.05. The dominant value in the physical work environment is 7.2%. The non-physical work environment also has a significant effect on employee performance with a sig. value of 0.00 <0.05 with a dominant value of 1.6%. In addition, the internal locus of control has a sig. value. 0.00 > 0.05, which means that partially, internal locus of control has a significant influence on employee performance. Internal locus of control has a dominant value of 64.3%, which means that internal locus of control has the most dominant value.